A Evaluasi Kesiapan Sekolah Tingkat SD dan SMP di Kabupaten Sumbawa dalam Pelaksanaan Pembelajaran tatap Muka Terbatas di Masa Pandemi Covis-19. - Has'ad Rahman Attamimi; Rusmayadi Rusmayadi; Yunita Lestari; Sudarli Sudarli; Ernawati Ernawati (Jurnal Penelitian Pendidikan IPA, 2022)
In September 2021, the Ministry of Education and Culture released the results of an internal survey, the survey results explained that there were 1,303 schools that became Covid-19 clusters. Of these figures, there were 7,287 teachers and 15,456 students exposed to the corona virus in Indonesia. So based on these conditions, an evaluation of school readiness will be carried out in implementing face-to-face learning programs during the Covid-19 pandemic. The evaluation will be carried out using the type of gap evaluation, where the evaluator will only measure the difference (gap) between what should be implemented (based on indicators of readiness for face-to-face learning during the Covid-19 pandemic) and the reality of the implementation being carried out. The evaluation method to be used is descriptive qualitative method with data collection techniques in the form of observation, interviews and document studies. The subjects in this evaluation were elementary and junior high schools in Kab. Sumbawa, and the object of evaluation are 7 indicators (requirements for limited face-to-face learning provided by the RI SATGAS Covid-19) readiness to implement limited face-to-face learning programs during the Covid-19 pandemic. The results of the evaluation of 84 primary school level and 8 junior high school level schools are in accordance with the results of observations, interviews and studies of supporting documents, in general it shows that the schools evaluated are ready to carry out face-to-face learning but a number of schools are still continuing to improve readiness in accordance with the required indicators both according to the PTM guidelines agreed upon by four ministers and the conditions given by the RI Covid-19 Task Force for 2021.